Estudo da degradação/desertificação no núcleo de São Raimundo Nonato - Piauí - Aquino, Cláudia Maria Sabóia de (2010)
Desertification is a serious problem in environments where it occurs, namely in dry lands (arid, semi-arid and dry sub-humid areas). This type of degradation affects about one quarter of the land surface, with implications for environmental, economic, political, social and cultural order. The areas in Brazil susceptible to this process are located in the northeast region which is characterized by low rainfall index, high temperatures, severe water deficit, shallow and rocky soils and xerophytic vegetation. São Raimundo Nonato, which is the object of this study, is located in the semi-arid region of Piaui and is a susceptible area to desertification. This has led to the study of degradation / desertification in this area in order to assess the risk of physical deterioration and effective degradation. The risk of physical deterioration was evaluated using the following indicators: climate, rainfall erosivity, erodibility of soils and slopeness. The effective degradation was assessed by considering the indicators discussed above combined with the NDVI of the years 1987 and 2007. The results indicate that 8.3%, 81% and 10.7% of the area are at risk of a low, moderate and high physical deterioration. The effective degradation, taking into account the NDVI for 1987, indicates that 70% and 30% of the area have respectively moderate and high degradation. For the year 2007, the data indicate that 71% and 29% of the area have respectively moderate and high effective degradation. These data reveal a dynamic ecological equilibrium with a subtle trend of improvement in terms of environmental degradation, that is , in the process of desertification in the studied area, since there is a reduction of the class of high effective degradation. The decline and economic stagnation in the area were found during the analysis of major crops and effective livestock . These data revealed a decline in the planted area, productivity and effective livestock, both in number of heads and / or unit of animals. The decline of these indicators corroborates the statement of improvement of environmental conditions in the studied area.